Perbandingan Konsep Misbruik Van Omstandigheden dan Undue Influence Dalam Kaitannya Dengan Pembentukan Klausula Baku Untuk Kredit Perbankan - Judanto, Muhammad Dhimas; Putra, Mohamad Fajri Mekka (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Misuse of circumstances in business practices in Indonesia is part of legal problems that often cause disputes between parties in business activities. Misuse of circumstances that generally occurs due to an imbalance in position between one party and another also occurs in the making of business agreements, especially in banking credit. The development of the concept of abuse of circumstances which initially developed in the Anglosaxon legal system which is known as undue influence, in its development later it was also known in the continental European legal system as misbruik van omstandigheden. In this legal research using normative juridical research methods, it will be analyzed regarding to the development of the concept of abuse of circumstances in the two existing legal systems in order to formulate the concept of abuse of circumstances that is in accordance with the times in the practice of forming standard clauses for bank credit. The results of this research will also compare the forms of legal protection for the parties in business practices against the potential abuse of circumstances that can occur in the formation of credit agreements.